A drive system to add standing mobility to a manual standing wheelchair. Issue 4 (1st October 2016) - Nickel, Eric; Hansen, Andrew; Pearlman, Jonathan; Goldish, Gary
ABSTRACT: Current manual standing wheelchairs are not mobile in the standing position. The addition of standing mobility may lead to improved health and function for the user and may increase utilization of standing wheelchairs. In this project, a chain drive system was fitted to a manual standing wheelchair, adding mobility in the standing position. The hand rims are accessible from both seated and standing positions. The prototype uses 16-inch drive wheels in front with casters in the rear. Additional anterior casters are elevated when seated for navigating obstacles and then descend when standing to create a six-wheeled base with extended anterior support. Stability testing shows the center of pressure remains within the base of support when leaning to the sides or front in both seated and standing positions. Four veterans with spinal cord injury provided feedback on the design and reported that mobility during standing was very important or extremely important to them. The veterans liked the perceived stability and mobility of the prototype and provided feedback for future refinements. For example, reducing the overall width (width from hand rim to hand rim) and weight could make this system more functional for users.